WLAN Security: Threats And Countermeasures - Suroto Suroto (JOIV : International Journal on Informatics Visualization, 2018)
A wireless local area Network (WLAN) is being widely recognized as a viable cost effective general purpose solution in providing high speed real time access to information. With a WLAN, users can gain access to shared information without being bound to fixed plug-in-point. WLAN transmit and receive data over the air and thus collectively combine data connectivity with ease of mobility. WLAN provides wireless access to multi location enterprises, small and medium enterprises. It can replace wired LAN or simply be used as extension of wired infrastructure. Besides all these advantages WLAN are also facing major problems of security.So security is the aspect where most of the researchers are working. Following are the major objective of our study : i) To study the various Vulnerabilities and attacks on WLAN and their solutions. ii) To study the some of the exiting security methods used for securing WLAN and explore the possibility of improvements in the same. Our conclusion that WLAN security is not easy, and it is constantly changing. They expose the network to a new group of hackers. All businesses need to determine their security requirements based on the application using the WLAN. Goal so that a WLAN is as protected as Wired LAN.